2010
DOI: 10.4995/wrs.2008.630
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transport duration and season on sensory meat quality in rabbits.

Abstract: ABSTRACT:Little is known about the effect that journey duration and position on the vehicle have on the sensory aspects of meat quality in rabbits. In this study, 156 rabbits were transported by road in a commercial truck for 1 h or 7 h in one of three replicates in summer or winter. After slaughter, slices from the left side of the longissimus dorsi muscle were vacuum-packaged and chilled at -18 ºC until the sensory analysis to assess odour, tenderness, juiciness, fi brousity, greasiness, and fl avour intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Rabbit odour and flavour were higher on average and more variable than liver odour and flavour. Our scores are in line with other sensory studies in rabbits in the same muscle (Gondret et al, 1998;Hernández et al, 2000;Gašperlin et al, 2006 andMaría et al, 2008). Table 5 shows ratios between LD 1 , LD 2 , LD 3 and LD 4 locations for sensory attributes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Rabbit odour and flavour were higher on average and more variable than liver odour and flavour. Our scores are in line with other sensory studies in rabbits in the same muscle (Gondret et al, 1998;Hernández et al, 2000;Gašperlin et al, 2006 andMaría et al, 2008). Table 5 shows ratios between LD 1 , LD 2 , LD 3 and LD 4 locations for sensory attributes.…”
Section: Discussionsupporting
confidence: 89%
“…Sensory attributes considered in the training are described in Table 1. These sensory attributes are commonly used in the evaluation of rabbit meat (see for example Hernández et al, 2000Hernández et al, , 2005Gašperlin et al, 2006 andMaría et al, 2008) or were suggested by the assessors in a preliminary session evaluating rabbit meat. Sensory attributes were trained individually and discussed in joint evaluations during 6 sessions of approximately 1 h each, distributed in 2 wk.…”
Section: Sensory Analysismentioning
confidence: 99%